Intersectoral collaboration and action in dengue vector control in Asia based on an eco-bio-social perspective - Pattamaporn Kittayapong (2022)
Complexity in the emergence of vector-borne diseases involves several components in the ecobio-social perspective. This makes it difficult for vector-borne disease control to be based solely on one organisation working on vector reduction. Dengue in particular involves (1) ecological components, such as the increase of breeding sites through changing a landscape (from rural to urban) and expansion of the range of mosquito habitats through climate change; (2) biological components, which mainly include human-vector-virus evolution and interaction in disease transmission; and (3) socio-economic components, such as insufficient household income and inadequate public health service. It is obvious that intersectoral collaboration with all relevant sectors to address these integrated components is one of the key criteria for successful vectorborne disease control. Intersectoral collaboration related to dengue has been mostly conducted when dengue control is in action, in order to enhance interventions aimed at vector control. In this chapter, different approaches of intersectoral collaborations and actions to control dengue in Asian countries by suppressing Aedes mosquito vectors will be highlighted. A few case studies include intersectoral collaboration for integrated vector management and innovative vector birth control. Based on the Asian experience, achieving intersectoral collaboration mainly involved the following key factors: (1) financial or technical support from within and outside participating sectors; (2) a clearly defined common interest which benefit all sectors; (3) a division of workload and joint management to achieve a common goal; (4) consistent coordination and communication among partnered sectors; (5) adaptability and flexibility in management; and (6) capacity building for sustainable intersectoral partnership.